(untitled) (CIPEEX, 2025)
Nurses play an indispensable role in the prevention and control of HAIs, leading the implementation of safe practices, training staff and ensuring that the necessary measures are strictly followed in all areas of healthcare. The role of this professional in the ICHC is not limited to direct control actions, but also includes the promotion of a culture of safety and continuing education for professionals, essential factors for reducing infection rates and improving health services. The aim of this study was to carry out an integrative review of the relationship between healthcare-related infections and nurses. To this end, this bibliographic study was carried out between February and November 2024, following the six stages of the Integrative Literature Review (ILR). Data was collected from indexed databases, using descriptors relatedto infections, healthcare and nursing. Articles published between 2019 and 2023, in Portuguese or English, with the full version available, were included. The critical analysis ofthe selected studies included exploratory reading, data extraction and organization of the results in a PRISMA flowchart and comparative table. After analyzing and interpreting the results, it was concluded that effectiveness in preventing and controlling healthcare-related infections depends on combining rigorous practices, such as hand washing and adherence to specific protocols, with continuous education and training for nurses. Integrating these approaches is essential for improving patient safety and reducing the impact of infections.